IoT-based Pyranometer Using Photodiode Sensor - Widiartha, Wahyu Dewa; Yohandri, Yohandri (Department of Physics, Universitas Negeri Padang, 2023)
Solar irradiance is one of the critical parameters of climatology because it is the driver of most of the dynamic processes in the atmosphere. We need a tool to measure solar irradiance, such as a pyranometer. However, the pyranometer has the disadvantage that it requires cables and electricity to send data to data processing devices, which sometimes causes data loss problems if the connecting cable is damaged unnoticed and a sudden power outage occurs. An IoT-based pyranometer using a photodiode sensor will overcome this problem because the tool will send the measured solar irradiance data directly to the internet. The objective of this research is to minimize the measurement data loss that occurs and to ensure the data quality. This is possible because the device operates with solar cells that constantly recharge the battery. This research is a type of engineering research. The measurement technique used is a direct measurement, comparing solar irradiance data with a standard pyranometer, then indirectly analyzing the accuracy and precision of the design tool. Based on direct testing of the tool, an accuracy and precision rate close to 100% was achieved, which was 98.19% and 98.63%, respectively. Therefore, it can conclude that the tool can work well. Moreover, measurements were also conducted at BMKG Sicincin on July 13, 2022 from 08:56 to 15:10, resulting in a measurement percentage of 4.87% with the highest solar irradiance at 12:15.